Conservation and historical distribution of two bumblebee species from the Atlantic Forest. Issue 1 (2nd January 2019) - Santos Júnior, José E.; Silveira, Fernando A.; Oliveira, Ubirajara; Dias, Cayo A. Rocha; Santos, Fabrício R.
Abstract : In this study, we analysed the processes resulting in the origin of two endemic sister species of bumblebees in the Brazilian Atlantic Forest. We studied the historical distribution pattern of Bombus bahiensis, which is restricted to small fragments in eastern Brazil and the phylogeographic pattern and historical demography of B. brasiliensis, which is widely distributed in southern and south-eastern Brazil and neighbouring regions of Uruguay, Paraguay, and Argentina. We used ecological niche models, niche analyses, and genetic and distribution data (i) to test the role of niche differentiation on the divergence between the two species, (ii) to find potential distribution areas for the most restricted B. bahiensis, and (iii) to evaluate the conservation status of both species. Our results showed that B. brasiliensis populations are able to disperse across mosaics of anthropogenic and preserved areas and exhibit low levels of spatial genetic structure. Otherwise, B. bahiensis presented a restricted distribution range and likely a lower diversity, where it is suffering with an increasing habitat loss. The climatic oscillations of the Pleistocene influenced the population structure of both species in different ways, probably due to differences in their effective population sizes, physiology and past demographic fluctuations. Specifically, while B. brasiliensis expanded its distribution range in the last 500, 000 years throughout most of the Atlantic Forest, B. bahiensis remained restricted to a small rainforest area between southern Bahia and northern Espírito Santo states in Brazil. In its southern distribution, in the state of Espírito Santo, B. bahiensis is currently very rare or extinct. Currently, the adjacent ranges of Bombus brasiliensis and B. bahiensis do not overlap and our results indicate that these species may have further diversified through a reinforcement process associated to niche specialization and differentiation.